Perioperative Management of Percutaneous Dilated Tracheostomy for Patient during Intensive Care after Ventriculoperitoneal (VP) Shunt Installation - Angky Hari Satriawan (Faculty of Medicine, Brawijaya University, 2021)
Background: Tracheostomy is a technique used to treat patients with inadequate ventilation and upper airway obstruction by making air passage through the neck directly into the trachea. Percutaneous dilated tracheostomy is usually performed in patients requiring long-term use of a ventilator in an intensive care unit. Basic knowledge of perioperative management of percutaneous dilated tracheostomy is fundamental and must be mastered by anesthesiologists.Case: A woman, 45 years old is treated at dr. Moewardi hospital with decreased consciousness E2V2M3, non-communicant hydrocephalus, and intraventricular hemorrhage. The patient underwent ventriculoperitoneal shunt surgery and was admitted to the intensive care unit. Patients require long-term use of a ventilator and thus require percutaneous dilated tracheostomy. The percutaneous dilated tracheostomy procedure was successfully performed and there were no complications after the procedure.Conclusion: Percutaneous dilated tracheostomy is a minimally invasive tracheostomy technique as an alternative to conventional techniques, with lower complications and shorter time.